The Measurement of Firm-Specific Indexes of Technical Change - Baltagi, Badi H.; Griffin, James M.; Rich, Daniel P. (The Review of Economics and Statistics, 1995)
This paper proposes a methodology for obtaining estimates of firm-specific technical change econometrically and contrasts those estimates with a multilateral total factor productivity index. Based on a panel data set of airlines, two measures are contrasted in a variety of ways. To the extent that output characteristics differ as in the case of airlines, the two measures differ significantly. Both measures are regressed on a variety of factors potentially influencing technical efficiency, confirming that improvements in fuel efficiency and load factor have played major roles, with hubbing and competition playing smaller roles, in explaining efficiency improvements. Copyright 1995 by MIT Press.